C3 Glomerulopathy: The Genetic and Clinical Findings in Dense Deposit Disease and C3 Glomerulonephritis - Xiao, Xue; Pickering, Matthew C.; Smith, Richard J. H. (Seminars in Thrombosis and Hemostasis, 2014)
C3 glomerulopathy (C3G) defines a group of very rare renal diseases in which dysregulation of the alternative and terminal complement pathways plays a pivotal pathogenic role. Dysregulation is driven by genetic and/or acquired defects, with interindividual variability giving rise to two broad subtypes of C3G—dense deposit disease (DDD) and C3 glomerulonephritis (C3GN). Patient evaluation should include genetic testing and biomarker profiling of complement activity. There is currently no effective targeted treatment option for C3G and, as a consequence, a variety of supportive measures are used. C3G remains an ideal disease in which new complement therapies can be tested as they become available. Trials must include a comprehensive evaluation of each patient at the genetic and biomarker level so that individual responses to therapy can be predicted and understood in light of the degree of complement dysregulation and underlying pathology.
Keywords: C3 glomerulopathy; dense deposit disease; C3 glomerulonephritis